WiMonitor: Continuous Long-Term Human Vitality Monitoring Using Commodity Wi-Fi Devices - Niu, Xiaopeng (Sensors (Basel), 2021)
For a large population of elderly who live alone, a continuous long-term daily monitoring system is critical and imminently needed to enhance the quality of their lives. Continuous monitoring of vitality information (i.e., which area the elder is staying in, the motion state and activity intensity of an elder) is essential for elderly care. In this paper, we use existing commodity Wi-Fi devices to design and implement a long-term device-free human daily vitality system, WiMonitor. Our system can continuously capture the target’s vitality information in a multi-room home environment without compromising the privacy of the target. In a continuous 22-day experiment, WiMonitor successfully captures the human vitality information accurately. We believe our system can provide valuable long-term monitoring data for both researchers and health care personnel.